PENGARUH GAYA KEPEMIMPINAN KEPALA INSTALASI FARMASI RUMAH SAKIT TERHADAP PENCAPAIAN KINERJA ORGANISASI DAN KEPUASAN KERJA - Nugroho, Dwi Agung; Rahem, Abdul; Hermansyah, Andi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
The Head of the Hospital Pharmacy Department (HPD) plays a vital role in achieving the department's performance goals. Each HPD adopts a unique leadership style that has implications for their job satisfaction. Therefore, it is necessary to examine the influence of the HPD's leadership style on performance achievement and job satisfaction. A survey was conducted using questionnaires. The questionnaire consisted of three instruments: the MLQ, The BSC, and a job satisfaction questionnaire . Spearman correlation analysis was used to evaluate the data. The transformational leadership had a significant positive impact on all dimensions of performance, with innovation being the most influenced dimension (r = 0.720, p < 0.01), as well as on motivation (r = 0.516, p < 0.01) and hygiene factors of job satisfaction (r = 0.613, p < 0.01). Transactional leadership also showed a positive relationship with performance but was less effective in enhancing job satisfaction. Conversely, laissez-faire leadership showed no significant relationship and even negatively affected innovation and motivation. Transformational leadership emerged as the most effective style for improving the performance and job satisfaction of HPDs in East Java, particularly in fostering innovation. Transactional leadership remains relevant for operational efficiency, while laissez-faire leadership should be minimized. The practical implications for the Head of the Hospital Pharmacy Installation are that the application of transactional and reward-based leadership styles is effective in improving staff performance in the short term, while transformational leadership is also important for building an innovative work culture, with a long-term empowerment and motivation approach